PI3K activation by IGF-1 is essential for the regulation of membrane expansion at the nerve growth cone - Laurino, Lisandro; Wang, Xiaoxin X; de la Houssaye, Becky A; Sosa, Lucas; Dupraz, Sebastian; Cáceres, Alfredo; Pfenninger, Karl H; Quiroga, Santiago (Journal of cell science, 2005)
Exocytotic incorporation of plasmalemmal precursor vesicles (PPVs) into the cell surface is necessary for axonal outgrowth and is known to occur mainly at the nerve growth cone. We have demonstrated recently that plasmalemmal expansion is regulated at the growth cone by IGF-1, but not by BDNF, in a manner that is quasi independent of the neuron's perikaryon. To begin elucidating the signaling pathway by which exocytosis of the plasmalemmal precursor is regulated, we studied activation of the IRS/PI3K/Akt pathway in isolated growth cones and hippocampal neurons in culture stimulated with IGF-1 or BDNF. Our results show that IGF-1, but not BDNF, significantly and rapidly stimulates IRS/PI3K/Akt and membrane expansion. Inhibition of PI3K with Wortmannin or LY294002 blocked IGF-1-stimulated plasmalemmal expansion at the growth cones of cultured neurons. Finally, our results show that, upon stimulation with IGF-1, most active PI3K becomes associated with distal microtubules in the proximal or central domain of the growth cone. Taken together, our results suggest a critical role for IGF-1 and the IRS/PI3K/Akt pathway in the process of membrane assembly at the axonal growth cone.